Jefferson Davis papers - Davis, Jefferson, 1808-1889.; Stephenson, Nathaniel W. (Nathaniel Wright), 1867-1935.
Correspondence, articles, speeches, photocopies of land grants, newspaper clippings, notes of historian Nathaniel W. Stephenson summarizing letters and writings by Davis which were printed in The War of the Rebellion : A Compilation of the Official Records of the Union and Confederate Armies (1880-1902), and drafts of military reports concerning the Battle of Monterrey (1846) in the Mexican War. Subjects include admission of California as a state, Mississippi state politics, a southern transcontinental railroad, and other prewar national issues. Correspondents include Amos B. Corwine, Hamlet J. Harris, William Maynadier, Philip A. Roach, and Crafts J. Wright.
Includes Varina Davis's correspondence, 1889-1906, relating primarily to her husband's capture on May 10, 1865; to family and personal matters; and to the conversion of Beauvoir, Davis's home in Biloxi, Miss., to a home for Confederate veterans.
Microfilm edition of a portion of these papers is available
Microfilm produced from originals in the Manuscript Division.
In part, photocopies.
Library of Congress Prints and Photographs Division.
President of the Confederate States of America.
Collection material in English.
Keywords: Corwine, Amos B. -- Correspondence; Davis, Varina, -- 1826-1906 -- Correspondence; Harris, Hamlet J. -- Correspondence; Maynadier, William, -- 1807-1871 -- Correspondence; Roach, Philip A. -- 1820-1889 -- Correspondence; Wright, Crafts J. -- 1808-1883 -- Correspondence; Davis family; Confederate States of America. -- Army; Mexican War, 1846-1848.; Monterrey, Battle of, Monterrey, Mexico, 1846.; Plantations -- Mississippi; Railroads -- Southern States; Beauvoir (Biloxi, Miss.) -- History; California -- Politics and government -- 1846-1850.; Confederate States of America -- History; Mississippi -- Politics and government; Southern States -- Politics and government; United States -- History -- 1815-1861.; United States -- History -- Civil War, 1861-1865.; United States -- History -- Civil War, 1861-1865 -- Veterans; Presidents -- Confederate States of America